Analisis Faktor Determinan Kinerja Keuangan pada Perusahaan yang Terdaftar di Bursa Efek Indonesia - Florentina, Jenny; Supriyanto, Supriyanto (Faculty of Economics, Universitas Internasional Batam, 2019)
This research is aimed to investigate determinant factors of firm performance especially listed companies at Indonesia Stock Exchange, using Return on Assets (ROA), Return on Equity (ROE), and Market-to-Book Value Ratio (MBR) as dependent variables. Determinants tested are current assets, leverage, cash flow, sales growth, investment in fixed assets, company characteristics, and income tax expense, with liquidity as control. Panel data regression is applied using secondary data in this study, with sample of companies with complete and audited annual financial statements for 2012-2017 period which are listed at Indonesia Stock Exchange. The results revealed current assets have significant negative effect on firm performance, while cash flow from operating activities, sales growth, and income tax expense significantly influence firm performance in positive. However leverage, investing and financing cash flow insignificantly influence firm performance. Firm characteristic overall has insignificant effect towards ROA and MBR but significantly determine ROE.